Physician altruism under the change from pure payment system to mixed payment schemes: experimental evidence - Yue Zhang; Xing Li; Xinyuan Zhang; Xinyan Li; Xing Lin; Youli Han (BMC, 2023)
Abstract Background Mixed payment schemes have become one of the effective measures to balance medical costs and quality of medical services. However, altruism as an intrinsic motivation may influence the effect of switching from a pure payment system to mixed payment schemes. This study aimed to quantify physicians' altruism and analyze the effect of changes of payment system on physicians' altruism and thus proposed references for the reform of payment system. Methods We simulated an exogenous payment system in a controlled laboratory with five experimental groups and 150 medical student subjects. Physicians' altruism was measured by estimating altruistic parameter and marginal rate of substitution. The non-parametric test and the least square regression analysis were used to analyze the differences of altruistic parameters between pure payment systems and mixed payment schemes. Finally, we analyzed the effect of changes in payment system accompanied by changes in trade-off range on physicians' altruism. Results We find that the mean value of individual altruistic parameter is 0.78 and the marginal rate of substitution is 1.078. Their estimates at the individual level were significantly positively correlated (Spearman's ρ = 0.715, p < 0.01). The shift from pure payment system to mixed payment scheme reduced the altruistic parameter. However, the altruistic parameter increased with the increase of the trade-off range. Physicians who were more altruistic generated higher patients' health benefit. For each unit increase in altruistic parameter, the increase in patients' health benefit was lower in mixed payment scheme than in the pure payment system. Conclusion The estimates of altruistic parameters are reliable. Physicians attach a higher weight to patients' benefit than to their own profit. Mixed payment schemes improve physicians' behavior and relate to lower altruistic parameters; physicians only need to sacrifice less personal profits to generate the same or even higher altruistic parameter as under the pure payment system. The design of mixed payment schemes that make the interests of physicians and patients close to each other by reducing the trade-off range can provide implication for the reform of payment system in which the physicians' interest and the patients' benefit are consistent.